ANALYZING THE RELATIONSHIP BETWEEN SERVICE SCIENCE, SERVICE INNOVATION, AND SERVICE ECONOMY - Fayziyev Bahodir (American Journals Publishing, 2025)
Based on service science and service innovation theory, this paper elaborates on the coupling relationship between innovation chain and industrial chain in the real industrial economy, and analyzes the internal reasons for the evolution of industries and the transformation of inter industry division of labor to intra industry division of labor. Analyzed the limitations of traditional economy and technological innovation, as well as the relationship between service activities and industrial value chains. Analyzed the relationship between service science, service innovation, and service economy, providing theoretical preparation for establishing a new type of service economy system.
Keywords: Service Science, service innovation, industrial evolution.